A Bioreactor Approach to Investigate the Linkage between Methane Oxidation and Nitrate/Nitrite Reduction in the Pelagic Oxic-Anoxic Transition Zone of the Central Baltic Sea - Jakobs, Gunnar; Labrenz, Matthias; Rehder, Gregor; Hietanen, Susanna; Kießlich, Katrin; Vogts, Angela; Blumenberg, Martin; Schmale, Oliver (Frontiers in Marine Science, 2016)
Evidence of aerobic methane oxidation coupled to denitrification has been provided for different freshwater environments, whereas the significance of this process for the marine realm has not been adequately investigated. The goal of this study was to investigate the methane-related reduction of nitrate/nitrite in a marine environment (salinity 8.5). A water sample was collected from the oxic-anoxic transition zone of the Gotland Deep (central Baltic Sea) and the microorganisms contained therein were cultivated in a bioreactor under hypoxic conditions (0.5 µM O2). To enrich the microorganisms involved in the coupled process the bioreactor was continuously sparged with methane as the sole energy and carbon source and simultaneously supplied with a nutrient solution rich in nitrate and nitrite. The bioreactor experiment showed a relationship between the turnover of methane and the concomitant concentration decrease of nitrite and nitrate at the early stage of the experiment. This relationship indicates the role of methanotrophs, which may support heterotrophic denitrifiers by the release of organic compounds as an energy source. Besides, a mixture of uncultured microorganisms, aerobic methanotrophic and heterotrophic denitrifying bacteria were identified in the enrichment culture. Microbial incorporation of nitrite and methane was proven on the cellular and gene levels via 15NO2- / 13CH4 incubation experiments and subsequent analyses with nano secondary ion mass spectrometry (NanoSIMS) and stable isotope probing (SIP). The NanoSIMS showed the incorporation of 15N in almost all the bacteria and in 9% of those there was a concomitant enrichment in 13C. The relatively low abundance of methane-consuming bacteria in the bioreactor was further reflected in specific fatty acids indicative for type I methanotrophic bacteria. Based on pmoA gene analyses, this bacterium is different from the one that was identified as the only key player of methane oxidation in previous studies in the Gotland Deep, indicating the existence of other subordinate methanotrophic bacteria at that site. The results provide the first indications for the predisposition of a methane-related reduction of nitrate/nitrite under hypoxic conditions in the marine realm, supporting the assumption of an interaction between methanotrophic and denitrifying bacteria which hitherto has only been described for fresh water environments.